Core competency-based strategy (London : International Thomson Business Press, 1997)
This book is divided into three parts: Understanding competencies; Competencies and corporate strategy; and Managing core competencies across business units.
Keywords: Business; Management; Strategic planning; Industrial management; Strategic planning; Business planning